Topical treatment targeting sphingosine‐1‐phosphate and sphingosine lyase abrogates experimental allergic rhinitis in a murine model. Issue 2 (18th December 2012) - KleinJan, A.; van, M.; Leman, K.; Hoogsteden, H. C.; Lambrecht, B. N.
Abstract Background Sphingosine‐1‐phosphate (S1P) plays a crucial role in homeostasis of the immune system by regulating lymphocyte recirculation and inflammatory cell recruitment. The levels of S1P are tightly controlled through regulated production and controlled breakdown by sphingosine‐lyase (SL). The S1P analogue FTY720 has been developed as an immunosuppressant in transplantation and tested as a treatment for various inflammatory diseases. FTY720 exploits S1P biology by acting as a S1P1 and S1P 3 agonist and by inhibiting S1P breakdown by SL. Objective Here, we investigate interfering S1P in allergic rhinitis (AR) and its way of action. Methods Allergic rhinitis was induced by sensitizing mice to ovalbumin (OVA) and challenging the nose with OVA allergen. At the time of allergen challenge, mice received topical intranasal treatment with FTY720. To address the relative contribution of SL inhibition in mediating its effects, some mice were treated with the SL inhibitor 2‐acetyl‐4‐tetrahydroxybutyl (THI). Results FTY720 treatment resulted in significantly fewer eosinophils, mast cells and dendritic cells in the nasal mucosa of AR animals, compared with diluent treatment. Levels of IL‐4, IL‐5, IL‐10 and IL‐13 produced by lymph node cells fell significantly in FTY720‐treated animals. Moreover, FTY720 proved potent enough to suppress inflammation in a model of persistent AR. In vitro and in vivo experiments indicate that FTY720 impaired Th2 differentiation and proliferation important in driving eosinophilia and induced apoptosis in mast cells. Conclusion Our results indicate that interfering with S1P metabolism is a powerful and feasible strategy to develop new topical agents that suppress AR.